1981
DOI: 10.1203/00006450-198106000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Hyperlipidemia in Children with Chronic Renal Insufficiency

Abstract: SummaryTotal serum cholesterol, phospholipids, and triglyceride levels, lipoprotein fractionation, and plasma parathormone levels were measured in a group of 31 nonnephrotic children with various levels of renal function and on hemodialysis. Group A served as controls and consisted of eight healthy children with glomerular fdtration rate (GFR) greater than 110 ml/min/1.73 m2. Group B consisted of six children with GFR of 60 to 95 ml/min/1.73 m2. Group C consisted of nine children with GFR of 10 to 40 ml/min/ 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
11
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
(30 reference statements)
4
11
0
Order By: Relevance
“…Similarly, those with severe renal failure had low LPL and HTGL activities. The hypertrig1yceridemia and the decreased HDL-C level in CRF reported in this study confirm the results of previous studies in children (20) and adults (16). The inverse correlation between serum TG and HDL-C levels in our patients was in keeping with the view that low HDL-C levels in hypertriglyceridemic states are the result of reduced TG metabolism (18).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similarly, those with severe renal failure had low LPL and HTGL activities. The hypertrig1yceridemia and the decreased HDL-C level in CRF reported in this study confirm the results of previous studies in children (20) and adults (16). The inverse correlation between serum TG and HDL-C levels in our patients was in keeping with the view that low HDL-C levels in hypertriglyceridemic states are the result of reduced TG metabolism (18).…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported both in adults (19) and children (20) that the hypertriglyceridemia occurs early in the course of renal insufficiency. In the present study, hypertriglyceridemia was observed even in patients with mild renal failure who had normal lipase activities.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study confirm previous reports that hypertriglyceridemia, Frederickson type IV, and low HDL-CH levels represent the most common dyslipidemic disorders in uremic children (1,5) as well as in uremic adults (2,4).…”
Section: Discussionsupporting
confidence: 81%
“…Hypertriglyceridemia, Frederickson type IV, associated with a consistent decrease in HDL-CH levels, represents the most common dyslipoproteinaemic disorder in these patients (1)(2)(3)(4)(5). Another unusual lipoprotein abnormality in uremic adults consists of an additional slow migrating pre-/3 VLDL band on AGE with an intermediate position between the regular fast-moving pre-/3 and /3…”
mentioning
confidence: 99%
“…While some of the abnormalities in these indices may recede after renal transplantation, others may persist [6]. In addition, serum TC levels are near normal, while LDL-C levels are variable [7][8][9][10][11][12][13][14]. …”
mentioning
confidence: 99%